TINJAUAN YURIDIS TERHADAP HAK EKONOMI PENCIPTA BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - ', Marzuki; Bachtiar, Maryati; Deliana, Evi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Economic rights are the exclusive right of an Authir or a Copyricght Holder to obtain economic benefits to the Work. Economic right may be transferred to a licensed party who has entered into an agreement with the creator. As for several matters which make economic rights an exclusive right, provided for in article 9 paragraph (1) of Law Number 28 Year 2014 concerning Copyright, Creator or Copyright Holder as reffered to in Article 8 has the economic right to do a.Publishing Creation; b.The copying of Creation in all its forms; c. The translation of Creation; d.Adjustment, arrangement, transform Creation; or e.Publication of Works or copies there of; f.Show Creation; g.Problems and objectives to be discussed in this thesis is to know how the form of protection of economicrights law creator.This type of research is normative, because iin this study the authors directly conduct research on legislation that regulates the copyright. The author’s research focus is on protecting the economic right of the creator, to see whether the protection afforded by lawis capable or not to protect the creator’s copyrighted work against the perpetrator of copyright infingemen.From the results of the study it can be concluded that the violation of the economic rights of the creator is still happening, the lack of legal awarenessof the community towards the protection of the economic rights of the creator is still one of the main obstacles in implementing the law and regulations of copyright, therefore the role of the law enforcer in implementing the law copyright is necessary, in order to create the protection of copyright law that is expected by the creator and able to encourage creativity of creators in the work with a sense of security because the creation of a copyright protection is expected during this.Keywords: Legal Protection – Economic Right – Creator – Copyright